TAHQIQ AN-NUSHUS ON AL-SYAFI'IY, AL-ALUSI AND AL-QUSYAIRI'S WORKS - Darni Yusna; Meirison Meirison; Ridho Nur (Majalah Ilmu Pengetahuan dan Pemikiran Keagamaan Tajdid, 2020)
Texts and manuscripts are the fields from which all knowledge begins, and concepts from various religions, laws, and historical documents are drawn from them. That is why texts in the Islamic heritage received special attention throughout the ages, and that included: texts: religion, history, intellectual. Throughout history, dealing with texts and investigating their content and form has become a stand-alone science and is needed for everyone who wants access to science. The work of as-Shafi'iy, Alusi, and Qusyairi were motivated by Islamic civilization in the process of investigation by paying attention to the science of Hadith and criticism of the Hadith, the creation of development and culminating in relative and plural truths. This generalization of knowledge develops and leads to historical, literary, and other texts (nushus), which contribute to the development of general rules and traditions to achieve a deeper understanding of shari'a texts and to divide the manuscripts and texts, between the true and the true weak or fake. The pioneers who worked on the art of science had appeared in the Arab world and set conditions and rules for it. Through this work, we aim to find out this critical reality, which is achieved by studying manuscripts and texts that were started by Arabs and Muslims.